2007
DOI: 10.1016/j.ejcb.2007.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Aging skeletal muscle shows a drastic increase in the small heat shock proteins αB-crystallin/HspB5 and cvHsp/HspB7

Abstract: Most heat shock proteins operate as molecular chaperones and play a central role in the maintenance of normal cellular function. In skeletal muscle, members of the a-crystallin domain-containing family of small heat shock proteins are believed to form a cohort of essential stress proteins. Since aB-crystallin (aBC/HspB5) and the cardiovascular heat shock protein (cvHsp/HspB7) are both implicated in the molecular response to fibre transformation and muscle wasting, it was of interest to investigate the fate of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
75
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 89 publications
(83 citation statements)
references
References 74 publications
(100 reference statements)
6
75
0
2
Order By: Relevance
“…Chemiluminescence substrate was purchased from Roche Diagnostics (Mannheim, Germany). Primary and secondary antibodies were obtained from various commercial sources, as listed in previous studies [16][17][18]. Ultrapure lysine for quenching the DIGE labeling reaction and all other analytical-grade chemicals were purchased from Sigma Chemical Company (Dorset, UK).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemiluminescence substrate was purchased from Roche Diagnostics (Mannheim, Germany). Primary and secondary antibodies were obtained from various commercial sources, as listed in previous studies [16][17][18]. Ultrapure lysine for quenching the DIGE labeling reaction and all other analytical-grade chemicals were purchased from Sigma Chemical Company (Dorset, UK).…”
Section: Methodsmentioning
confidence: 99%
“…Several mass spectrometry-based proteomic studies have investigated changes in the protein complement of aging skeletal muscles over the last few years, as reviewed by Doran et al [13]. These proteomic profiling studies have focused on crude soluble extracts and have shown that muscle aging is associated with altered expression levels of many key contractile proteins, regulatory elements, ion handling proteins, metabolic enzymes and mediators of the cellular stress response [14][15][16][17][18][19][20]. The proteomic finding of a drastically decreased density and reduced enzymatic activity of certain glycolytic enzymes in senescent fibres [21] is in agreement with the idea of a fast-to-slow transformation process during aging [13].…”
Section: Introductionmentioning
confidence: 99%
“…Comparative studies were performed with young adult (3-month-old), adult (6-month-old) and senescent (30-monthold) tibialis anterior, gastrocnemius and soleus preparations. Muscle specimens (100 mg wet weight) were pulverized in liquid nitrogen using a mortar and pestle, and the resulting powder was placed into 1 ml of homogenisation buffer consisting of 0.5 M HEPES, pH 7.4, 200 mM EGTA, 10% (w/v) sucrose, 3 mM MgCl 2 solution and 0.1% (w/v) NaN 3 , as well as a protease inhibitor cocktail (Doran et al, 2007). Tissue suspensions were sonicated for 10 s, subsequently incubated on ice with vortexing every 10 min for 10 s over a 4 h period, and then centrifuged for 20 min at 20,000g.…”
Section: Preparation Of Aged Muscle Specimensmentioning
confidence: 99%
“…Gels were stained with Coomassie Blue or transferred to nitrocellulose membranes at 100 V for 70 min using a Transblot Cell from BioRad Laboratories (HemelHempstead, Herts., UK). Blocking, washing, incubation with antibodies and enhanced chemiluminescence detection of immuno-decorated proteins was carried out by optimized methodology (Doran et al, 2007).…”
Section: Gel Electrophoretic Separation and Immunoblot Analysismentioning
confidence: 99%
See 1 more Smart Citation